Design of inherent fire retarding and degradable bio-based epoxy vitrimer with excellent self-healing and mechanical reprocessability. (10th November 2022) - Yang, Weijun; Ding, Hui; Zhou, Wei; Liu, Tianxi; Xu, Pengwu; Puglia, Debora; Kenny, Jose M.; Ma, Piming
Abstract: Epoxy resins possess poor flame retardancy and have difficulty in both recycling and reprocess ability which largely limit their application. Herein, two vanillin-based epoxy monomers, shorted as VAD-EP and VDP-EP, containing both imine bonds and inherently fire retarding phosphorus elements, were synthesized via in situ condensation reaction with DDM and addition reaction with DOPO, followed by the epoxidation by epichlorohydrin. Epoxy vitrimer materials were then cured by D230 diamine hardener by adjusting the proportion of VAD-EP and VDP-EP monomer. When the mass ratio of VAD-EP and VDP-EP was 8:2, A8 P2 -D230 reached the fire retarding UL-94 V0 rating and LOI value of 27.0% with only 0.66% of phosphorus content, this behavior was ascribed to condensed phase and free radical scavenging mechanisms. When the mass ratio was 7:3, the tensile strength and elastic modulus of the A7 P3 -D230 epoxy were 75.5 MPa and 2.5 GPa, respectively, i.e. 48.6% and 18.8% higher than A10 P0 -D230 sample. Meanwhile, the material showed high stress relaxation rate, due to the presence of dynamic imine bonds in the topological crosslinking network. As a consequence, the epoxy vitrimer exhibited excellent self-healing capability, reprocessability and degradation behaviors. The biobased epoxy vitrimer was then used to prepare the carbon fibers (CFs) reinforced epoxy composites, results showed that CFs can be completely recycled. Interestingly, the recycled CFs maintain unchanged chemical structure, mechanical properties and morphology as the original CFs. Graphical abstract: Image 1